Evolution of tail fork depth in genus Hirundo. Issue 3 (18th January 2016) - Hasegawa, Masaru; Arai, Emi; Kutsukake, Nobuyuki
Abstract: A classic example of a sexually selected trait, the deep fork tail of the barn swallow Hirundo rustica is now claimed to have evolved and be maintained mainly via aerodynamic advantage rather than sexually selected advantage. However, this aerodynamic advantage hypothesis does not clarify which flight habits select for/against deep fork tails, causing diversity of tail fork depth in hirundines. Here, by focusing on the genus Hirundo, we investigated whether the large variation in tail fork depth could be explained by the differential flight habits. Using a phylogenetic comparative approach, we found that migrant species had deeper fork tails, but less colorful plumage, than the other species, indicating that migration favors a specific trait, deep fork tails. At the same time, tail fork depth but not plumage coloration decreased with increasing bill size – a proxy of prey size, suggesting that foraging on larger prey items favors shallower fork tails. Variation of tail fork depth in the genus Hirundo may be explained by differential flight habits, even without assuming sexual selection. Abstract : Using a phylogenetic comparative approach, we found that migrant Hirundo species had deeper fork tails, but less colorful plumage, than the other Hirundo species, indicating that migration favors a specific trait, deep fork tails. At the same time, tail fork depth but not plumage coloration decreased with increasing bill size, suggesting that foraging on larger prey items favors shallower fork tails. Variation of tail fork depth in the genus Hirundo may be explained by differential flight habits, even without assuming sexual selection.